The Effectiveness of Artificial Intelligence-Based Animated Video Education on Elementary School Students’ Dental Health Knowledge - Caesary Cloudya Panjaitan; Khairunnisa Salsabilla; Goalbertus; Trijani Suwandi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Oral health problems among children remain high due to limited knowledge and poor hygiene habits. The 2023 Indonesian Health Survey reported that 50.9% of the population experience oral health problems, while only 3.4% practice proper toothbrushing. Engaging educational media are therefore needed. Artificial intelligence (AI)–based animated videos provide interactive visual and audio content that is easily understood by children. This study evaluated their effectiveness in improving dental and oral health knowledge among elementary students. Materials and Methods: This quasi-experimental study used a one-group pretest–posttest design involving 53 fourth-grade students of SDN 146/VIII Rejosari. Dental health education was delivered using AI animated video media. Knowledge was assessed using a 19-item questionnaire before and after the intervention and categorized into good, sufficient, and poor. Data were analyzed using a paired t-test (p < 0.05). Results and Discussions: Before the intervention, most students had poor knowledge (69.81%), followed by sufficient (26.42%) and good (3.77%). After education, the good category increased to 52.83%, sufficient decreased to 39.62%, and poor decreased to 7.55%. Paired t-test results showed a significant improvement (p < 0.001). Conclusion: AI animated videos effectively improve elementary students’ dental and oral health knowledge.